Biallelic somatic SMARCA4 mutations in small cell carcinoma of the ovary, hypercalcemic type (SCCOHT). Issue 4 (12th October 2014) - Bailey, Shivani; Murray, Matthew J.; Witkowski, Leora; Hook, Elizabeth; Hasselblatt, Martin; Crawford, Robin; Foulkes, William D.; Tischkowitz, Marc; Nicholson, James C.
<x xml:space="preserve">Abstract</x> Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare, aggressive tumor that primarily affects young women. SCCOHT has recently been identified as a monogenic disorder caused by germline and/or somatic SMARCA4 mutations. We describe a 15‐year‐old Caucasian female with a SCCOHT harboring a previously unreported somatic mutation in the SMARCA4 gene (c.1757delA; p.K586.fs) with loss of heterozygosity. No germline mutation was identified. Subsequent immunohistochemical staining confirmed loss of SMARCA4 protein. These molecular findings will aid with SCCOHT diagnosis through immunohistochemical staining for SMARCA4 and in the future may have implications for the management of this disease. Pediatr Blood Cancer 2015;62:728–730. © 2014 Wiley Periodicals, Inc.